STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Masyhuri Masyhuri; Aliman Aliman (Manajer Pendididikan, 2019)
This study determined the efforts made by the principal in improving the professional competence of IPS Geography teacher at SMA Negeri 1 Lintang Kanan. This research uses descriptive qualitative approach. Data collection techniques are done through interviews, and documentation. Research subjects were Headmaster, Vice Principal, and Geography Teacher at SMA Negeri 1 Lintang Kanan. The results showed that: (1) Principal Strategy in improving the competence of Professional Teachers IPS Geography in the development of teaching materials has been interpreted well; (2) Principal Strategy in improving the professional competence of IPS Geography teacher in the use of teaching methods to examine the readiness of learning plan (RPP) consisting of effective weeks, annual program, semester program, syllabus, learning, assessment (KKM), as well as lesson plans made together with similar subject teachers; (3) Principal Strategy in improving the professional competence of IPS Teachers Geography in evaluating implementation learning by looking at readiness in performing task assignment, daily test, block, semester final repetition.